2010
DOI: 10.1159/000315405
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Exposure to Lead, Mercury, and Selenium and the Development of Amyotrophic Lateral Sclerosis and the Epigenetic Implications

Abstract: Metal exposures are an intriguing potential culprit in the cause of sporadic amyotrophic lateral sclerosis (ALS). For one, there are numerous case reports linking different metals to an ALS phenotype. Furthermore, some investigators have demonstrated higher levels of certain metals in the blood, bone, cerebrospinal fluid, urine, or spinal cords of patients with ALS compared to controls. There are also many case-control studies looking at the possible association of certain metals with the development of ALS. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 94 publications
3
61
0
Order By: Relevance
“…Some metals investigated as implicated in ALS are correlated to the mercury (Hg) and cadmium. Mercury may be implicated as a risk factor for development of the pathology [78]. Clinical ALS symptoms in patients accidentally exposed to Hg [79] have been observed in a work published by Schwarz et al [79].…”
Section: Etiology Of Als As Well As the Onset Mechanismsmentioning
confidence: 91%
See 1 more Smart Citation
“…Some metals investigated as implicated in ALS are correlated to the mercury (Hg) and cadmium. Mercury may be implicated as a risk factor for development of the pathology [78]. Clinical ALS symptoms in patients accidentally exposed to Hg [79] have been observed in a work published by Schwarz et al [79].…”
Section: Etiology Of Als As Well As the Onset Mechanismsmentioning
confidence: 91%
“…Observing the conflicting evidence in the literature regarding the role of Hg in the etiology of ALS, is hoped to bring about a greater interest in this topic [84]. [78] review some evidence leads to the hypothesis that an interaction between heavy metal exposure and an individual's genetic makeup is required to produce epigenetic changes that ultimately lead to ALS DDT -dichlorodiphenyltrichloroethane; ELF-EMF -extremely low-frequency electromagnetic field; MET -metabolic equivalent. role in the gene expression control, may be involved in the complexity of the disease in its phenotypes and progression [91][92][93].…”
Section: Etiology Of Als As Well As the Onset Mechanismsmentioning
confidence: 99%
“…Including such factors as occupation, heavy metals, petro‐chemicals, organophosphate/pesticides26, 27, 28, 29, 30 and possible influence of electromagnetic field (EMF)18, 25, 31 and military service 32. Although not all studies related to ALS have consistently reported environmental factors,33 the majority have highlighted environmental factors rather than longevity4, 5, 6, 7, 8, 18, 25, 26, 27, 28, 29, 30 as well as epigenetic changes,33, 34, 35 whist recently, research had linked rises in dementias to proximity to major roads 30…”
Section: Discussionmentioning
confidence: 99%
“…Lead, a toxic compound can induce adverse effects in each biological system by damaging hematopoietic, nervous, renal, cardiovascular, immune and reproductive system [1,2]. Engine exhaust from traffic vehicles is the primary source of toxicity of lead because it contains various toxic chemicals that are hazardous for the human body [3].…”
Section: Introductionmentioning
confidence: 99%